Evolution of blood pressure in children with congenital and acquired solitary functioning kidney - Riccardo Lubrano; Isotta Gentile; Raffaele Falsaperla; Giovanna Vitaliti; Alessia Marcellino; Marco Elli (BMC, 2017)
Abstract Background It is not yet clear if blood pressure and renal function changes evolve differently in children with a congenital or acquired solitary functioning kidney. This study aims to assess if there are any differences between these two types of solitary kidney patients. Methods Current research is a retrospective study assessing the evolution of glomerular filtration rate, proteinuria, and blood pressure in clinical records of 55 children with a solitary functioning kidney (37 congenital and 18 acquired). We used the medical records of children who had been assisted, in our unit of pediatric nephrology, for a period of 14 years (168 months), from the time of diagnosis, between January/1997 and December/2015. Results During the study period, glomerular filtration rate (T0 128.89 ± 32.24 vs T14 118.51 ± 34.45 ml/min/1.73 m2, p NS) and proteinuria (T0 85.14 ± 83.13 vs T14 159.03 ± 234.66 mg/m2/die, p NS) demonstrated no significant change. However, after 14 years of follow-up 76.4% of patients had increased levels of arterial hypertension with values over the 90th percentile for gender, age, and height. Specifically, children with an acquired solitary functioning kidney mainly developed hypertension [T0 2/17 (12%) vs T14 9/17 (52.9%) p < 0.025], whereas children with a congenital solitary functioning kidney mainly developed pre-hypertension [T0 3/38 (7.9%) vs T14 17/38 (44.7%) p < 0.0005]. Conclusions The renal function of children with solitary functioning kidneys remains stable during a follow-up of 14 years. However, these children should be carefully monitored for their tendency to develop arterial blood pressure greater than the 90th percentile for gender, age, and height.